AN OVERVIEW ON THE ABUSE OF POWER IN THE PERSPECTIVE OF CORRUPTION LAW AND GOVERNMENT ADMINISTRATION LAW IN INDONESIA BASED ON THE CRIMINAL JUSTICE SYSTEM AND THE STATE ADMINISTRATION OF THE JUSTICE SYSTEM - Gumbir, Seno Wibowo; Nurhayati, Ratna (Yustisia, 2016)
AbstractThe abuse of power in Indonesia has been  regulated in the realm of administrative law at the Law Number 30 Year 2014 on Government Administrationand Law Number 31 Year 1999 jo Law Number  20 Year 2001 on The Corruption Eradication. The arrangement in those lawshas created an overlapping, overcriminilization and disharmony of law. This can be seen in Law  No 30 Year 2014 on Goverment Administration,the sanctions of  the abuse of powerare simply to return loss and can also be accompanied by dismissal, while in Law No 31 Year 1999 jo Law Number 20 Year 2001 onthe Eradication of Corruption with or without loss can be imprisoned and returning the loss will not remove the criminal prosecution. Other than that, there are potential linkage in the test to determine a state officials discretions between the Administrative Court and the Constitutional Court Post Pretrial Judicial Review Decision to extend the authority of the Pretrial.